Modified graphene for energy conversion and storage applications - Xiao, Ni (2014)
In current society, global energy consumption has been rising at an astonishing speed because of the massive use of the electrical machines and equipments. Practically, electrical energy is the end product of many power processes. So study of electrical energy conversion and storage is a meaningful job towards practical applications.